NF-AB, a liver-specific and cytokine-inducible nuclear factor that interacts with the interleukin-1 response element of the rat alpha 1-acid glycoprotein gene. - Won, K A (1991)
The 142-bp cytokine response element of the rat alpha 1-acid glycoprotein (AGP) gene is a complex of several additively contributing regulatory sequences. By using deletions and point mutations, a minimal interleukin-1 (IL-1) response element was localized to the region from positions 1 to 36 within the 5'-most AB fragment of the cytokine response element. Two distinct sequence motifs were contained within this element, both of which were required to achieve full IL-1 response in rat and human hepatoma cells. This element showed a minor response to phorbol ester treatment only in human hepatoma cells. Southwestern (DNA-protein) blot analysis of nuclear proteins of rat liver and hepatoma cells revealed the presence of a heat-labile nuclear factor (NF-AB). NF-AB migrated as a basic protein with an apparent molecular mass of 37 kDa and bound specifically to the DNA sequence at positions 10 to 37 of the AB fragment. The NF-AB binding activity was detected neither in the cytoplasmic fraction of rat hepatoma cells nor in nuclear extracts from control or acute-phase rat kidney. The binding activity of NF-AB correlated with the transcriptional activity of the endogenous AGP gene in rat liver and hepatoma cells. Nuclear extract from human HepG2 cells showed a similar binding activity with an apparent molecular mass of 34.5 kDa. The human NF-AB binding activity was detectable only after 13 h of cytokine treatment and was not induced by phorbol ester. Tissue distribution, DNA sequence binding specificity, and kinetics of cytokine induction of NF-AB do not coincide with the characteristics of any other described factors that have been associated with cytokine regulation. Therefore, NF-AB is considered a new candidate involved in IL-1 regulation of the rat AGP gene.